Pericoronary and periaortic adipose tissue density are associated with inflammatory disease activity in Takayasu arteritis and atherosclerosis. Issue 2 (6th August 2021) - Wall, Christopher; Huang, Yuan; Le, Elizabeth P V; Ćorović, Andrej; Uy, Christopher P; Gopalan, Deepa; Ma, Chuoxin; Manavaki, Roido; Fryer, Tim D; Aloj, Luigi; Graves, Martin J; Tombetti, Enrico; et al.
Abstract: Aims: To examine pericoronary adipose tissue (PCAT) and periaortic adipose tissue (PAAT) density on coronary computed tomography angiography for assessing arterial inflammation in Takayasu arteritis (TAK) and atherosclerosis. Methods and results: PCAT and PAAT density was measured in coronary ( n = 1016) and aortic ( n = 108) segments from 108 subjects [TAK + coronary artery disease (CAD), n = 36; TAK, n = 18; atherosclerotic CAD, n = 32; matched controls, n = 22]. Median PCAT and PAAT densities varied between groups (mPCAT: P < 0.0001; PAAT: P = 0.0002). PCAT density was 7.01 ± standard error of the mean (SEM) 1.78 Hounsfield Unit (HU) higher in coronary segments from TAK + CAD patients than stable CAD patients ( P = 0.0002), and 8.20 ± SEM 2.04 HU higher in TAK patients without CAD than controls ( P = 0.0001). mPCAT density was correlated with Indian Takayasu Clinical Activity Score ( r = 0.43, P = 0.001) and C-reactive protein ( r = 0.41, P < 0.0001) and was higher in active vs. inactive TAK ( P = 0.002). mPCAT density above −74 HU had 100% sensitivity and 95% specificity for differentiating active TAK from controls [area under the curve = 0.99 (95% confidence interval 0.97–1)]. The association of PCAT density and coronary arterial inflammation measured by 68 Ga-DOTATATE positron emission tomography (PET) equated to an increase of 2.44 ± SEM 0.77 HU in PCAT density for each unit increase in 68 Ga-DOTATATE maximum tissue-to-blood ratio ( P = 0.002). These findings remained in multivariable sensitivity analyses adjusted for potential confounders. Conclusions: PCAT and PAAT density are higher in TAK than atherosclerotic CAD or controls and are associated with clinical, biochemical, and PET markers of inflammation. Owing to excellent diagnostic accuracy, PCAT density could be useful as a clinical adjunct for assessing disease activity in TAK. Graphical Abstract: